A Stylistic Investigation: Verbal Parallelism in Reverend Budde’s 2025 U.S. Presidential Inauguration Prayer Service Sermon - Ludwina Victoria Sielke Laurent Sopacuaperu; Fithriyah Inda Nur Abida; Widyastuti Widyastuti; Lina Purwaning Hartanti (Hasanuddin University, 2025)
Verbal parallelism is a stylistic device frequently employed in public and religious discourse to enhance rhythm, emphasis, and memorability. This study investigates the use of verbal parallelism in Reverend Mariann Budde’s sermon delivered at the 2025 United States presidential inauguration prayer service. The research aims to explore how verbal parallelism functions stylistically in the sermon and how it contributes to highlighting key messages. A qualitative research design was employed, using documentation and analysis of the sermon transcript as the primary data source. The analysis identified eight types of verbal parallelism based on Leech’s (1969) classification. The findings revealed that seven types verbal parallelism was deliberately and systematically used throughout the sermon. Anaphora was found to be the most frequently used type, followed by homoioteleuton, epistrophe, symploce, polyptoton, anadiplosis, and antistrophe. On the whole, this study confirms that verbal parallelism serves as an effective stylistic strategy in public and religious discourse.